Assessing the role of ghrelin and the enzyme ghrelin O-acyltransferase (GOAT) system in food reward, food motivation, and binge eating behavior. (October 2021) - Micioni Di Bonaventura, Emanuela; Botticelli, Luca; Del Bello, Fabio; Giorgioni, Gianfabio; Piergentili, Alessandro; Quaglia, Wilma; Cifani, Carlo; Micioni Di Bonaventura, Maria Vittoria
Abstract: The peripheral peptide hormone ghrelin is a powerful stimulator of food intake, which leads to body weight gain and adiposity in both rodents and humans. The hormone, thus, increases the vulnerability to obesity and binge eating behavior. Several studies have revealed that ghrelin's functions are due to its interaction with the growth hormone secretagogue receptor type 1a (GHSR1a) in the hypothalamic area; besides, ghrelin also promotes the reinforcing properties of hedonic food, acting at extra-hypothalamic sites and interacting with dopaminergic, cannabinoid, opioid, and orexin signaling. The hormone is primarily present in two forms in the plasma and the enzyme ghrelin O-acyltransferase (GOAT) allows the acylation reaction which causes the transformation of des-acyl-ghrelin (DAG) to the active form acyl-ghrelin (AG). DAG has been demonstrated to show antagonist properties; it is metabolically active, and counteracts the effects of AG on glucose metabolism and lipolysis, and reduces food consumption, body weight, and hedonic feeding response. Both peptides seem to influence the hypothalamic–pituitary–adrenal (HPA) axis and the corticosterone/cortisol level that drive the urge to eat under stressful conditions. These findings suggest that DAG and inhibition of GOAT may be targets for obesity and bingeing-related eating disorders and that AG/DAG ratio may be an important potential biomarker to assess the risk of developing maladaptive eating behaviors. Graphical Abstract: ga1 Highlights: Ghrelin impacts food reward by increasing mesolimbic dopamine transmission. Ghrelin interacts with dopaminergic, cannabinoid, opioid, and orexin signaling. GOAT inhibition is a pharmacological tool to block the orexigenic effect of ghrelin. Ghrelin influences HPA axis activity and bingeing-related eating disorders. Ghrelin system dysregulation increases the risk of obesity and binge eating behavior.